Hubungan Konsumsi Asupan Protein, Zat Besi Dan Vitamin C Dengan Kadar Hemoglobin Pada Ibu Hamil Di Desa Joho Kecamatan Mojolaban Kabupaten Sukoharjo - OKTAVIA MANDASARI, RACHMAWATI, Dwi Sarbini, S.ST., M.Kes, Dr. Mutalazimah, SKM, M.Kes (2015)
Pregnant mother is a group of persons who have high risk of anemia. Beside iron substance deficiency, anemia could happen because of others nutrient deficiency. The protein intake has a role in the iron substance transportation in a whole body. Iron is the main component in the blood forming. Vitamin C has the character to be the promoter towards iron absorption. Purpose: Knowing the relationship between protein intake consumption, iron substance, and vitamin c towards haemoglobin rate in pregnant mothers in Joho Village Mojolaban Sub-District Sukoharjo Regency. Research Method: This research is an observational research with sectional approach. The amount of research subject is 50 persons chosen by proportional random sampling method. The protein intake consumption data, iron substance, and vitamin C are achieved by using Recall 24 hours. Furthermore, the hemoglobin rate data is achieved by using cyanmethemoglobin test. The data analysis technique of protein intake consumption is person product moment. Moreover, the iron substance and vitamin C consumption data are analyzed by rank sperman. Result: The result shows that 62.0% research subjects have deficit protein intake consumption, 74.0% research subjects have lack of iron substance consumption, 50.0% research subjects have enough vitamin C intake consumption, and 60% research subjects have normal haemoglobin rate. The result of correlation test for protein intake consumption with haemoglobin rate is p=0.649, the iron substance consumption with haemoglobin rate is 0.259, and vitamin C intake consumption with haemoglobin rate is p=0.463. Conclusion: There is no relationship between protein intake consumption, iron substance, and vitamin C towards haemoglobin rate in pregnant mothers in Joho Village Mojolaban Sub-district Sukoharjo Regency.